2018
DOI: 10.1186/s41235-018-0117-4
|View full text |Cite
|
Sign up to set email alerts
|

Face recognition ability does not predict person identification performance: using individual data in the interpretation of group results

Abstract: There are large individual differences in people’s face recognition ability. These individual differences provide an opportunity to recruit the best face-recognisers into jobs that require accurate person identification, through the implementation of ability-screening tasks. To date, screening has focused exclusively on face recognition ability; however real-world identifications can involve the use of other person-recognition cues. Here we incorporate body and biological motion recognition as relevant skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 67 publications
1
44
0
Order By: Relevance
“…Interestingly, both face matching and memory were only moderately predictive of searching performance, although any associations with personality facets remained unclear or absent. Previous work has suggested that performance on a test of face matching may be unable to predict performance on body‐ and biological motion‐based tests, perhaps highlighting the limitations of focussing on face abilities when attempting to determine how people may perform with other types of identification (Noyes, Hill, & O'Toole, ). Researchers might also consider whether other individual differences might better predict search abilities, and related, whether those who are established as high performers on other face tasks (e.g., super recognisers; Russell et al, ) will also excel on this type of test.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, both face matching and memory were only moderately predictive of searching performance, although any associations with personality facets remained unclear or absent. Previous work has suggested that performance on a test of face matching may be unable to predict performance on body‐ and biological motion‐based tests, perhaps highlighting the limitations of focussing on face abilities when attempting to determine how people may perform with other types of identification (Noyes, Hill, & O'Toole, ). Researchers might also consider whether other individual differences might better predict search abilities, and related, whether those who are established as high performers on other face tasks (e.g., super recognisers; Russell et al, ) will also excel on this type of test.…”
Section: Discussionmentioning
confidence: 99%
“…Their point is that the criteria used to define a super-recognizer may depend on the demands of the real-world job. Specifically, the error rate that is acceptable in one situation may be different from another, and the task that the super-recognizer will need to perform may also be critical if super-recognizers do turn out to differ from each other (Noyes, Hill, & O'Toole, 2018). Whilst we have given reasons to question whether existing evidence does point unequivocally to different types of super-recognizers, this is clearly an open and fundamental question.…”
Section: Commentarymentioning
confidence: 98%
“…Specifically, the error rate that is acceptable in one situation may be different from another, and the task that the super-recognizer will need to perform may also be critical if super-recognizers do turn out to differ from each other (Noyes, Hill, & O'Toole, 2018). But if super-recognizers are indeed at the top end of the distribution of ability, we think it makes sense to place them in jobs that match their skill.…”
Section: Commentarymentioning
confidence: 99%
“…The recruitment of these specialist groups in applied settings has proceeded on the assumption that the laboratory‐based tests – developed by or with scientists – are sufficient to select people that will perform well in real‐world deployment . However, operational tasks (see Figure ) can involve complex and diverse challenges, which – in addition to processing of face‐related visual information – may also entail the use of multiple identity cues that are not confined to the face (c.f., Rice, Phillips, Natu, An, & O'Toole, ; Noyes et al ., ). As a result, systematic analysis of real‐world tasks should be the starting point for development of recruitment and selection tests.…”
Section: Introductionmentioning
confidence: 97%
“…When considering other abilities that may predict performance in real‐world tasks such as CCTV review and surveillance, this problem is more acute. For example, the ability to match a person based on body cues does not appear to correlate with performance on face identity processing tasks (Noyes, Hill, & O'Toole, ), suggesting that face processing tasks are not sufficient to capture abilities that may be pertinent to operational deployment.…”
Section: Introductionmentioning
confidence: 99%